The effect of local potential-based biology learning resources on students' competencies: An in-depth analysis - Fajeriadi, Hery; Azzam, Muhammad Naufal; Azzahra, Fatimah Ghina (Universitas Negeri Jakarta, 2025)
This research stems from the low utilization of local potential-based biology learning resources in schools, despite their importance in deepening biological understanding, shaping student character, and fostering environmental awareness, amid growing challenges like resource exploitation, land use change, and climate change. This study aims to assess how effective biology learning resources based on local potential affect student attitudes and learning outcomes by conducting a systematic literature review and meta-analysis using the PRISMA method on articles published between 2013 and 2024. The main data source came from Google Scholar, focusing on articles discussing the utilization of local potential as a learning resource. The uniqueness of this method lies in the categorization of articles based on dependent variables, namely student attitudes and learning outcomes. The data were analyzed descriptively for attitude variables and quantitatively using Cohen's d formula to measure the effect size on learning outcomes for articles with adequate data. The results of the analysis showed that local potential-based learning significantly impacted positively on students' attitudinal changes (including environmental awareness and conservation) and improved cognitive learning outcomes, as seen from high N-gain and effect size values. These findings support the application of contextual and constructivist approaches that are in line with the Merdeka Curriculum, which emphasizes the importance of strengthening character and sustainability. In conclusion, learning resources based on local potential can improve learning quality and shape students with character and environmental awareness, while strengthening empirical evidence on contextual biology education and learning based on local wisdom.